Freinet Pedagogy: Enduring Impact Over an Individual Career - John Sivell (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article presents an individual perspective on the impact of Freinet Pedagogy across the career of one English language teacher and teacher educator. With special attention to language instruction, I will highlight a number perennially important Freinet dimensions that gradually came to my attention over the years. My admiration for Freinet Pedagogy first arose in relation to two very hands-on techniques: free writing and classroom printing. Later, my interest took a more theoretical turn, through recognition of illuminating consistencies between Freinet Pedagogy and two other more recent developments: broadly, van Lier's (2004) influential ecological perspective on language learning may be taken as a backdrop against which to highlight the coherence of Freinet Pedagogy both with the flexibly system-based style of planning now advocated by such authorities as Reason (2008), and with the present-day connectionist psychological approach to opportunities for language teaching and learning that has been metaphorically represented in back-to-the-well terms (Sivell & Sivell, 2012).